A systematic literature review on necessity,challenges, applications and attacks of watermarking relational database - Alfagi, Abdalrahman; Abd Manaf, Azizah; Hamida, Belal Ahmed; Hamza, Mohd. Ghazli. Hamza (Universiti Teknikal Malaysia Melaka, 2017)
Systematic literature review (SLR) is a significant research methodology in software engineering and computer science. One precarious step in applying this methodology is to enterprise and perform appropriate and effective search approach. This is a time-consuming and error-prone step, which needs to be carefully planned and implemented. There is an apparent need for a systematic approach to designing and performing a suitable search strategy for optimally retrieving the target literature from digital libraries. To the best of our knowledge, five intensive review papers [1-5] have been found which are not SLR, instead they are a normal survey or literature review. In contrast to [1-9] this paper followed general guidelines for undertaking SLR in order to illustrate necessity, challenges, applications, and attacks of watermarking relational database. An advanced search has been performed in most relevant digital libraries to obtain potentially relevant articles published until the end of 2014. Forty-six primary studies (PSs) have been identified based on inclusion and exclusion criteria. The analytical study is mainly based on the PSs to achieve the objectives. The results illustrate the importance of digital watermark in protecting the relational database, the differences between watermarking relational database and multimedia objects and the demand to increase the level of attack resilience. In addition, the results indicate that watermarking relational database is an interested area for researchers.